Value chain analysis of movable frame hive honey: The case of Ahferom Woreda, Tigray, Ethiopia - Mehari, A. (Aksum University, 2015)
This study aims at analyzing value chain of movable frame hive honey in Ahferom Woreda of Tigray region with specific objective of identifying the honey value chain actors, functions, activities, and degree of coordination; assessing profit distribution of participants in the honey value chain; identifying factors affecting market channel choice decision of honey producers and identifying constraints and opportunities of honey value chain in the study area and to propose mechanisms to upgrade the value chain. The data were collected from both primary and secondary sources. The primary data for this study were collected from120 beekeepers, 6 traders, 45 consumers using pre-tested questioner. This was supplemented by secondary data from different published and unpublished sources. The result of the descriptive statistics showed that, the majority of the honey producers in the study area were male households. Value chain analysis revealed that the major actors in the Woreda are input suppliers, beekeepers, local collectors, retailers and consumers. The activities performed by the actors in the survey period were input supply, production, marketing and consumption. It is also found that honey passes through intermediaries with little value being added before reaching the final users. The result of market structure-conduct-performance indicates the presence of strong oligopoly market structure. The multinomial logit model result indicates that, the probability to choosing collector channel was positively and significantly affected by producers’ previous agreement with buyers and negatively and significantly affected by average monthly income and market information compared to consumers’ outlet. Similarly, the probability of choosing retailers channel was positively and significantly affected by age, beekeeping experience, distance to nearest market and market information compared to consumers’ outlet. The result of ranking index indicated that, honey production was constrained by prevalence of pests and predators, agro chemical application and lack of beekeeping tools and equipments. Despite this there are also opportunities such as availability of area closures, easy access to modern beekeeping materials, availabilities of bee’s forages, motivating government policy, and high demand for quality and quantity of honey. Therefore, policy aiming at gender consideration, capacity development, establishing honey collection centers, developing and improving infrastructure, market information and adequate supply of beekeeping tools and equipments are recommended to accelerate honey value chain development.